2021
DOI: 10.20525/ijrbs.v10i6.1364
|View full text |Cite
|
Sign up to set email alerts
|

The effect of e-service quality on e-loyalty mediated by e-trust and brand image variables

Abstract: The amount of e-wallet providers in Indonesia is so many, so there is intense competition between each e-wallet provider. The tighter competition for e-wallet, makes users not only loyal to one type of e-wallet and makes users switch brands or providers in using an e-wallet. This study aims to investigate the factors that influence e-service quality on e-loyalty mediated by e-trust and brand image. This research is categorized as explanatory research. Respondents in this study were users of the OVO e-wallet ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 21 publications
9
15
0
3
Order By: Relevance
“…It means that the higher the E-Service Quality, the higher the brand image tends to be. This study supports previous research (Pratiwi, Sunaryo and Mugiono, 2021;Kang and Chung, 2018;Alipoor, 2016) which stated that e-service quality has a positive and significant effect on brand image. The result of this study shows that if Shopee Food can provide quality e-service well, it will create a great Shopee Food brand image in the minds of Shopee Food users.…”
Section: Resultssupporting
confidence: 92%
“…It means that the higher the E-Service Quality, the higher the brand image tends to be. This study supports previous research (Pratiwi, Sunaryo and Mugiono, 2021;Kang and Chung, 2018;Alipoor, 2016) which stated that e-service quality has a positive and significant effect on brand image. The result of this study shows that if Shopee Food can provide quality e-service well, it will create a great Shopee Food brand image in the minds of Shopee Food users.…”
Section: Resultssupporting
confidence: 92%
“…This is because customers tend to prefer to use products or services from brands that have a positive reputation. This is also in line with research conducted by Tam et al (2022); Pratiwi et al (2021); Permatasari et al (2022) which states that there is a significant positive relationship between Brand Image and Continuance Intention. Therefore, this raises the following hypothesis:…”
Section: Brand Imagesupporting
confidence: 91%
“…The ease of interacting with customer service or technical support can also affect customers' perception of the brand. Overall, E-Servicescape plays an important role in shaping the brand image of a company or brand, this is in line with research conducted by Widiani et al (2022);Iskandar et al (2018); Pratiwi et al (2021); Lowry et al (2008); Permatasari et al (2022) which states that there is a significant positive relationship between E-Servicescape and Brand Image. Therefore, this raises the following hypothesis:…”
Section: Brand Imagesupporting
confidence: 87%
“…And the result is that e-service quality significantly affects e-loyalty mediated by brand image. So, it can be concluded that the quality of e-service can increase e-loyalty by building a positive brand image (Pratiwi et al, 2021). This is also supported by research conducted by Chen & Liu, who proposed the formulation of the fourth hypothesis: brand image mediates the quality relationship.…”
Section: Hypothesis and Modelmentioning
confidence: 64%